2016
DOI: 10.1111/jam.13198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature (5-25°C) on epiphytic lactic acid bacteria populations and fermentation of whole-plant corn silage

Abstract: This study demonstrated the impact of temperature gradient on the diversity and some important population shift of lactic acid bacteria communities during fermentation of corn silage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 61 publications
11
95
5
Order By: Relevance
“…In our study, populations of yeasts and moulds in the fresh forage were greater than the previous studies with maize silage (Assis et al., ; Filya, ; Zhou et al., ). This difference in population could be attributed to factors such as maize hybrid, maturity and environmental conditions.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In our study, populations of yeasts and moulds in the fresh forage were greater than the previous studies with maize silage (Assis et al., ; Filya, ; Zhou et al., ). This difference in population could be attributed to factors such as maize hybrid, maturity and environmental conditions.…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have investigated the diversity of epiphytic LAB during the maize ensiling process. In general, L. plantarum and P. pentosaceus were the predominant LAB species in the beginning of fermentation, whereas L. buchneri and L. brevis were widely detected few days after ensiling (Brusetti et al, 2006;Lin, Bolsen, Brent, & Fung, 1992;Parvin, Wang, Li, & Nishino, 2010;Stevenson, Muck, Shinners, & Weimer, 2006;Zhou et al, 2016). It is generally recognized that to produce a high-quality silage, the fermentation should start with homofermentative LAB species.…”
Section: Isolation and Identification Of Lab From Tropical Maize Simentioning
confidence: 99%
See 1 more Smart Citation
“…; Zhou et al . ). In tropic and sub‐tropic regions, the longer period of hot weather is considered a main factor that results in poor‐quality silage.…”
Section: Introductionmentioning
confidence: 97%
“…Such silages are often found to have high pH value, low rate of pH decline (Ali et al 2015) and low acid production (Kung 2010). Zhou et al (2016) reported that low temperature could reduce fermentation efficiency by lowering the growth rate and enzymatic activity of micro-organisms. Even, the commercial lactic acid bacteria (LAB) inoculants might be inhibited and are thus not effective at low temperatures (Kim and Uchida 1990;Weinberg and Muck 1996).…”
Section: Introductionmentioning
confidence: 99%